Analysis of Occupational Safety and Health Implementation in National Strategic Projects Case Study of Kulon Progo Airport Infrastructure Development Project - Pakpahan, Daniel Rinsani; Hermawan, Ferry; Ismiyati, Ismiyati (International Journal of Social Service and Research, 2023)
This project has challenges in the form of work complexity, the use of a large number of various types of heavy equipment, thousands of workers with various skills, and a very short time to complete the work. The purpose of this study is to analyze the factors that influence the Construction Safety Management System (CSMS), analyze the risk level of project implementation, and evaluate the effectiveness of CSMS performance implementation in the Kulon Progo Airport Infrastructure Development Project which is expected to be able to provide lessons learned from other similar projects. The research method used is a qualitative method using HSE activity reports during the construction period and interviews with seven informants who were involved during the construction period. The results of the study show that there are ten top ranking keys to the success of CSMS in the Kulon Progo Airport Infrastructure Development Project, including Hazard Identification, Risk Assessment, Control and Opportunity, Job Safety Analysis (JSA), Communication, Concern with training programs, Occupational Health Management, Work Environment Safety Management, Equipment,  Construction Safety Unit Duties and Responsibilities, Standards and Legislation as well as Inspections and Audits.